Universal Access to Surgical Care and Sustainable Development in Sub-Saharan Africa: A Case for Surgical Systems Research; Comment on "Global Surgery - Informing National Strategies for Scaling Up Surgery in Sub-Saharan Africa" - Emmanuel M. Makasa (Kerman University of Medical Sciences, 2019)
National level experiences, lessons learnt from the Millennium Development Goal (MDG) era coupled with the academic evidence and proposals generated by the Lancet Commission on Global Surgery (LCoGS) together with the economic arguments and recommendations from the World Bank Group's "Essential Surgery" Disease Control Priorities (DCP3) publication, provided the impetus for political commitments to improve surgical care capacity at the primary level of the healthcare system in low- and middle-income countries (LMICs) as part of their drive towards universal health coverage (UHC) in the form of World Health Organization (WHO) Resolution A68.15. This global commitment from governments must be followed up with development of a Global Action Plan and a global coordination mechanism supported by regional implementation frameworks on the part of the WHO in order for the organisation to better coordinate all stakeholders and sustain the technical support needed to develop and implement national surgical health policy in the form of National Surgical Obstetric and Anaesthesia Plans (NSOAPs). As expounded by Gajewski et al, data and research output on surgical care is essential to informing policy development and programme implementation. This area still remains a challenge in sub-Saharan Africa (SSA) but it is envisaged that countries will include this key component in their ongoing national surgical healthcare policy development and programme implementation. In the Zambian case study, research in the area of Global Surgery investment-the surgical workforce scale-up is used to demonstrate the important role of implementation research in the development and implementation of the Zambian NSOAP as well as the need for international collaborations to this end. Scale-up reviews informed by implementation research to evaluate progress on the commitments contained in Resolution A68.15 and Decision A70.22 are essential to sustain the momentum and to help maintain focus on the gaps in all countries. There are opportunities for non-state actors especially local sub-regional academic institutions, non-governmental organizations (NGOs) and private sector to play a key role in surgical healthcare policy development and implementation research. Collection of and better information management of standardised surgical care indicators is essential for such research, for bi-annual WHO progress reporting and for demonstration of impact to justify and encourage further investments in surgical care.